The Communication Effectiveness of Online Learning Tax Education in Makassar Utara Tax Office - Riffat Khairi; Andi Alimuddin Unde; Tuti Bahfiarti (Universitas Darussalam Gontor, 2022)
In early 2020, Indonesia and almost all countries worldwide faced the Covid-19 pandemic. The government issued a regulation to implement online learning activities in the education sector. Responding to the regulation, the Directorate General of Tax issued a policy stating that the dissemination activities can be done online. Effective communication is needed to fill the gap between information delivered by the dissemination officer and taxpayers' understanding. Therefore, the online tax education in the Makassar Utara Tax Office is required to be presented attractively to change the taxpayers' behaviors. The present study aims to analyze the communication effectiveness in online tax dissemination held by the Makassar Utara Tax Office. Conducted in the Makassar Utara Tax Office, this quantitative action research involved 105 taxpayers classified as high compliance risk, recruited using a probability sampling technique. The primary data were collected using a questionnaire, while the secondary data were gathered from literature and the Makassar Utara Tax Office reports. The study found that online learning communication in tax dissemination was very effective. Most taxpayers access tax-related information more than five times a year to fulfill their tax obligation. Most taxpayers stated that the online dissemination was presented attractively, clearly, and relevant to their tax-related needs.